Pelatihan Penulisan Sitasi Menggunakan Aplikasi Mendeley Untuk Mahasiswa Tingkat Akhir - Riana, Riska Iva; Ilmi, Nurul; Muflihat, Syakia; Baharuddin, Siti Ruqaiyah; Fauziah, Fauziah (Jurusan Matematika FMIPA UNM, 2025)
Writing citations and bibliographies is an important part of writing scientific papers, especially for final year students who are writing their thesis or final assignment. However, many students still have difficulty in applying correct and consistent citation rules. Therefore, this training aims to improve students' understanding and skills in using the Mendeley application as a reference management tool. The training activities were carried out directly and were divided into several sessions, including an introduction to the concept of citation, installation and use of the Mendeley application, as well as the practice of inserting citations and creating automatic bibliographies in Microsoft Word. The training participants were final year students from the Automotive Engineering Education Study Program, who were selected based on the need to improve academic literacy skills. The results of the pre-test and post-test showed a significant increase in the participants' understanding and skills. In addition, feedback obtained through the questionnaire showed that the majority of participants felt that this training was very useful and relevant. Thus, this training can be one solution to help students improve the quality of scientific papers and avoid plagiarism.